SISTEM PENANGANAN KELUHAN SARANA DAN PRASARANA IT BERBASIS WEB (STUDI KASUS : UNIVERSITAS SAHID SURAKARTA) - Arya Kumara Adji (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2022)
Sahid University Surakarta is equipped with adequate IT (information technology) facilities and infrastructure, and its development is very rapid. The development of IT facilities and infrastructure (information technology) requires the active role of PSIT in preparing and solving IT facilities and infrastructure problems on campus. In solving problems, many obstacles occur on the platform used by PSIT. The study aims to build a web application for the Complaint Handling System for IT Facilities and Infrastructure at Sahid University, Surakarta. SIMKIT is a computer system for managing complaints data for new IT infrastructure facilities to solve the PSIT problem. This study used the waterfall method as a system development method. Data collection techniques used literature study, interviews, document analysis. The analysis and design used the Unified Modeling Language (UML), while the test used the webqual 4.0 method and SPSS statistical data processing. In the complaint handling system for IT facilities and infrastructure, there are 3 actors who have access, namely Complainants, PSIT Officers, and Administrators. Complainants (Students, Lecturers, and Employees of Sahid University Surakarta) have access to submit their complaints on the platform in the system. PSIT officers have access to handle incoming complaints from Complainants and provide feedback if the complaints have been handled. The administrator has full web access to process the web add or change content on the administrator page. SIMKIT has a mobilefriendly concept that can be accessed through various devices, and the method used UML. The results of this study indicate that the usability quality of the SIMKIT web application is easy to use and the SIMKIT web application design is in accordance with the type of desktop and mobile-friendly website that can be accessed on several devices. The quality of the information presented on the SIMKIT web application is easy to understand. On the quality of service interaction, this SIMKIT web application provides space for accessible communication. In the overall user satisfaction assessment, users are satisfied with the performance of the SIMKIT web application.